Study of the Performance of Particles Based on Modified Starches Containing Potassium Sorbate and Incorporated into Biodegradable Films: Physicochemical Characterization and Antimicrobial Action - Alzate Calderón, Paola Carolina (2021)
Ultrasound technique was used to produce native and acetylated cassava starch particles containing potassium sorbate (KS). In order to obtain an active packaging, films with addition of native starch particles containing KS (NKSPF) or added with acetylated starch particles containing KS (AKSPF) were formulated. As control systems, films without KS (CF) or added with KS that was not retained in particles (KSF), were produced. The NKSPF and AKSPF microstructure was consistent with composite materials. Tensile test revealed that CF and KSF were ductile and extensible (stress at break (σb) 2.8–2.5 MPa and strain at break (εb) 284–206%), while NKSPF and AKSPF were more resistant films with higher Young’s Modulus (148–477 MPa) and σb (3.6–17 MPa) but lower εb (40–11%). Moreover, NKSPF and AKSPF developed lower Yellowness Index (6.6–6.5) but higher opacity (19–23%) and solubility in water (31–35%) than KSF (9, 10.8% and 9%, respectively). It was observed that KSF and NKSPF moderately reduced the Zygosaccharomyces bailii growth while AKSPF showed the highest yeast inhibition, three Log-cycles, compared to CF. Additionally, FTIR spectroscopy revealed intensified interactions between KS and modified starch. It was concluded that starch sonication and acetylation were useful modifications to produce particles carrier of KS that improved the physical and antimicrobial performance of active films.